ORGANIC INTELLECTUALS AND INORGANIC AGITATORS. SPAIN, ITALY AND FRANCE. 12TH CENTURY - Astarita Rojas, Carlos (Revista de Historia Social y de las Mentalidades, 2024)
Are studied here some of the agitators and  intellectuals who perfomed in communal  revolutions in the Middle Ages. Methodological  considerations are made about the sources.  With the chronicles speeches are analized. Also  conditions under which the acted and they were  educated.
Keywords: Middle Ages; Communal revolutions; Agitators and intellectuals